A look into the realm of Room-Temperature Superconductors - González, J.C. (2021)
Condensation of hydrogen atoms into solid-state (metallic) under high pressure (500 GPa) was one key experimental fact in this millennium. Triggering a race to explore the conditions necessary to produce a metallic state in metal-hydride compounds under high-pressures by using a diamond anvil cell, although some laboratories did not only obtain others compounds in metallic-state, they also achieved the superconducting state. In October 2020, carbon, sulfur and hydrogen compound became room-temperature superconductor (287,7 K) under pressure close to 267 GPa, sparking again the interest in superconducting materials, and coming back one more time the dream of the technological applications of room-temperature superconductors without cooling liquid.